Significant enhancement of structural stability of the hyperhalophilic ADH from Haloferax volcanii via entrapment on metal organic framework support - Carucci, Cristina; Bruen, Larah; Gascón, Victoria; Paradisi, Francesca; Magner, Edmond (ACS Publications, 2018)
The use of an in-situ immobilization procedure for the immobilization of hyperhalophilic alcohol dehydrogenase in a metal organic framework material is described. The easy and rapid in situ immobilization process enables retention of activity over a broad range of pH and temperature together with a decrease in the halophilicity of the enzyme. The catalytic activity of the immobilized enzyme was studied in non-aqueous solvent mixtures with the highest retention of activity in aqueous solutions of methanol and acetonitrile. The approach demonstrates that this immobilization method can be extended to hyperhalophilic enzymes with enhancements in activity and stability.